The Application of Menstrual Hygiene Management towards the Elementary Students Hygiene Personal Attitude during Menstruation - Nur Asnah Sitohang; Diah Lestari; Cut Adeya Adella; Nu Asiah (Talenta Publisher, 2025)
The main problem among adolescents related to menstruation is the lack of knowledge about Menstrual Health Management (MHM) and poor water sanitation. This study aims to determine the effectiveness of MHM on the knowledge and personal hygiene behavior of elementary school students in Medan. The research employed a quasi-experimental design with a one-group pretest-posttest approach. The population is all elementary school students in grades 4 and 5. The sample included 67 female and 43 male students, totaling to 110 participants. Data were collected using a questionnaire administered before the intervention (pretest), followed by a health education program consisting of lectures, discussions, and role plays, supported by LCD/PowerPoint presentasions, leaflets, and videos, and then after the intervention (posttest).The sampling technique used was total sampling. Dependent t-test analysis was utilized to assess the data. The results showed a significant difference in respondents’ knowledge before and after the intervention. For attitudes, the mean difference was 3.440 with a p-value of 0.000, indicating a significant effect of the intervention on respondents’ attitudes. Specifically, for male students, the mean difference in knowledge was 7.721 (p = 0.000), and the mean difference in attitudes was 1.628 (p = 0.000), confirming a significant improvement in both knowledge and attitudes after the intervention. Therefore, it is recommended that health workers implement MHM education programs to improve adolescent reproductive health status. Keyword: Menstrual hygiene knowledge, Attitude, Elementary student management